A Review of Groundwater Pollution Potential Threats from Municipal Solid Waste Landfill Sites: Assessing the Impact on Human Health - Priyanka Kumari; N.C. Gupta; A. Kaur (Hamadan University of Medical Sciences, 2017)
An attempt has been made in this paper to review various studies associated with groundwater contamination near landfill sites, basically caused by non-engineered landfills or open dumps in India and overseas, and its impact on human health. Landfill leachate contains different kinds of municipal toxic wastes as well as heavy metal, which finally percolates into the ground and joins the groundwater table. Consuming such water results in severe health hazards and may sometimes be fatal if consumed for long periods. Several studies have shown evidence on the high concentration of heavy metals in leachate as well as in nearby groundwater sources. Moreover, various studies have confirmed the fact that there is an increased threat of adverse health effects (low birth weight, birth defects, and certain types of cancers), congenital malformations in children, and higher risks for malformations of the nervous and musculoskeletal systems for skin, hair, and nails in local residents. Pregnant women and children are more vulnerable to these pollutants, and newborn children are more prone to the health risk. These findings may signify the real health risks associated with residents residing near landfill sites.